Answer: subtract 5 from both sides
Explanation: get rid of the 5 before moving on to isolating the variable
Answer:
A) ![\sqrt{2}](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D)
B) ![4\sqrt{11}](https://tex.z-dn.net/?f=4%5Csqrt%7B11%7D)
Step-by-step explanation:
A) You can add these expression because they contain the same square root:
![6\sqrt{2} - 5\sqrt{2} = (6 - 5)\sqrt{2} =\sqrt{2}](https://tex.z-dn.net/?f=6%5Csqrt%7B2%7D%20%20-%205%5Csqrt%7B2%7D%20%3D%20%286%20-%205%29%5Csqrt%7B2%7D%20%3D%5Csqrt%7B2%7D)
B) Same as above:
![\sqrt{11} + 3\sqrt{11} = (1 + 3)\sqrt{11} = 4\sqrt{11}](https://tex.z-dn.net/?f=%5Csqrt%7B11%7D%20%2B%203%5Csqrt%7B11%7D%20%3D%20%281%20%2B%203%29%5Csqrt%7B11%7D%20%3D%204%5Csqrt%7B11%7D)
Answer:
4c² + 11cd + 5d
Step-by-step explanation:
(–4c2 + 7cd + 8d) + (–3d + 8c2 + 4cd)
-4c² + 7cd + 8d - 3d + 8c² + 4cd (opening bracket)
8c²-4c²+7cd + 4cd + 8d - 3d
= 4c² + 11cd + 5d
Answer:
2823908
Step-by-step explanation: